Data repository for "Increase in insurance losses caused by North Atlantic hurricanes in a warmer climate" ... - Comola, Francesco (Mendeley Data, 2024)
This data is associated with the article "Increase in insurance losses caused by North Atlantic hurricanes in a warmer climate". The dataset contains the script used to reproduce the results presented in the paper. - "HurricanePaper2024_repo.R" contains the R script that can be used to generate the results presented in the paper. ...